Isolation of H2S-generating Bacterium (Desulfovibrio sp.) and Vibrio parahaemolyticus From Aquatic Farming and In Vitro Evaluation of the Ability of Bacteriophages as Biocontrol - Truong Thi Bich Van; Nguyen Thi Loan Anh; Nguyen Huu Tri; Chau Thanh Tuan (Jurnal Ilmiah Perikanan dan Kelautan)
Graphical Abstract